Trends of Top IS Research by Region, Outlet, and Emergence: A Semi-Automated Literature Review - Nadine Guhr; Oliver Werth; Jens Passlick; Michael H. Breitner (Information, 2023)
Global trends towards the rapidly increasing use of information systems (IS) apply to the IS research domain and related publications. Nonetheless, investigations of trends in publication behavior and emergence as well as changes in IS research are usually narrowly focused. This article contributes to the growing number of articles published in the IS domain by analyzing the evolution of trends and major research fields as well as the regional distribution of publications in the AIS Senior Scholars’ Basket of Eight (AIS Bo8) and the International Conference on Information Systems (ICIS), changes in publication behavior, and the emergence of as well as changes to IS research fields and trends. Our semi-automated literature review integrates scientific methods to support the review and classification of publications. Based on 6692 articles published in the ICIS proceedings and the AIS Bo8 journals in a period of 16 years, we elaborate the key characteristics of research development. Our contribution provides and interprets a contemporaneous account of contextual factors influencing the IS research domain. Thus, our study enhances understanding of the development of the IS research domain.